Head-Down-Tilt Bed Rest With Elevated CO2: Effects of a Pilot Spaceflight Analog on Neural Function and Performance During a Cognitive-Motor Dual Task - Mahadevan, Aditya D.; Hupfeld, Kathleen E.; Lee, Jessica K.; De Dios, Yiri E.; Kofman, Igor S.; Beltran, Nichole E.; Mulder, Edwin; Bloomberg, Jacob J.; Mulavara, Ajitkumar P.; Seidler, Rachael D. (Frontiers in Physiology, 2021)
Spaceflight has widespread effects on human performance, including on the ability to dual task. Here, we examine how a spaceflight analogue comprising 30 days of head-down-tilt bed rest combined with 0.5% ambient CO2 (HDBR+CO2) influences performance and functional activity of the brain during single and dual tasking of a cognitive and a motor task. The addition of CO2 to HDBR is thought to better mimic the conditions aboard the International Space Station. Participants completed three tasks: (1) COUNT: counting the number of times an oddball stimulus was presented among distractors; (2) TAP: tapping one of two buttons in response to a visual cue; and (3) DUAL: performing both tasks concurrently. Eleven participants (6 males) underwent functional MRI (fMRI) while performing these tasks at six time points: twice before HDBR+CO2, twice during HDBR+CO2, and twice after HDBR+CO2. Behavioral measures included reaction time, standard error of reaction time, and tapping accuracy during the TAP and DUAL tasks, and the dual task cost (DTCost) of each of these measures. We also quantified DTCost of fMRI brain activation. In our previous HDBR study of 13 participants (with atmospheric CO2), subjects experienced TAP accuracy improvements during bed rest, whereas TAP accuracy declined while in the current study of HDBR+CO2. In the HDBR+CO2 subjects, we identified a region in the superior frontal gyrus that showed decreased DTCost of brain activation while in HDBR+CO2, and recovered back to baseline levels before the completion of bed rest. Compared to HDBR alone, we found different patterns of brain activation change with HDBR+CO2. HDBR+CO2 subjects had increased DTCost in the middle temporal gyrus whereas HDBR subjects had decreased DTCost in the same area. Five of the HDBR+CO2 subjects developed signs of spaceflight-associated neuro-ocular syndrome (SANS). These subjects exhibited lower baseline dual task activation and higher slopes of change during HDBR+CO2 than subjects with no signs of SANS. Collectively, this pilot study provides insight into the additional and/or interactive effects of CO2 levels during HDBR, and information regarding the impacts of this spaceflight analogue environment on the neural correlates of dual tasking.